Membangun Fondasi Keuangan yang Kokoh: Workshop Literasi Keuangan untuk Guru Madrasah Nurul Haq, Lombok Tengah - Jumaedi, M.; Muhtarom, Zamroni Alpian; Budiman, Budiman; Wafik, Ahmad Zaenal; Ilham, M. Rozi Fatwa (Lembaga Yasin AlSys, 2026)
Financial literacy is an essential skill that directly influences individual well-being and quality of life, including within the educational context. As agents of change, madrasah teachers hold a strategic role in instilling literacy values in students; however, they continue to face challenges in managing personal finances due to limited income and low financial awareness. This community engagement initiative aimed to enhance the financial literacy of teachers at Madrasah Nurul Haq, Central Lombok, through an interactive workshop held on 11 June 2025, involving 20 participants. The implementation methods included socialization, material presentation, guided discussions, financial planning training, introduction to the myIFPE Syariah application, and evaluation through pre-test and post-test assessments. The results indicate an average increase of approximately 50% in participants’ financial literacy scores after the training. Participants responded positively to the content, considering it relevant, applicable, and beneficial for managing personal and household finances. Challenges such as limited access to digital devices and varying levels of digital literacy were effectively addressed through intensive mentoring and the provision of spreadsheet-based alternatives. This initiative proved effective in raising financial awareness and enhancing teachers’ financial management capacity and is recommended to be continued through the establishment and strengthening of financial literacy groups within the madrasah environment.